Faith, Spirituality, and Character: An Overview of The Qur’ānic Principles of a Successful Life - Hafiz Abdul Ghani; Hafiz Saeed Ahmad (Universitas Ahmad Dahlan, 2023)
From Aristotle’s Nicomachean Ethics to modern psychologists such as Martin Seligman (b.1942), it has been an old-age human quest to know the principles of success, happiness, and fulfillment. In the rapidly changing modern world, defining the concept of a ‘successful and happy life’ through the teachings of various philosophies has become an important and popular study. A great number of self-help books and research articles are being published to teach the principles and practices of success. Different ideologies and philosophers suggest different principles of success. Some of which may be effective while some may not be. It is important to explore the most authentic and reliable principles of success. For this article, the literature review of the Qur’ānic verses has been conducted under a governing question: What is true success, and how to attain it in the light of Qur’ān? The goal of this study is to identify the Qur’ānic view and principles of success and examine their validation for immediate socioeconomic success as well as the ultimate bliss. This article has attempted to define the concept of true success, explore the best pathway to success, and elaborate on the essential principles of fulfillment in the light of Islam. The researchers have used the qualitative method to analyze Qur’ānic verses with deductive reasoning as their research methodology.